Ethical Awareness, Perceived Usefulness, and AI Literacy Predict University Students’ Intentions to Use AI Tools - Muhammad Ghazi Saputra; Elsa Wulandari Tambunan; Andi Nurhalisa Dwiani; Devi Miftahul Jannah; Saif Mohammed (Artificial Intelligence in Lifelong and Life-Course Education, 2026)
Purpose – This study examines how ethical awareness and perceived usefulness shape university students’ intentions to use artificial intelligence tools, and whether artificial intelligence literacy mediates these relationships in higher education.Design/methods/approach – A quantitative cross-sectional survey was administered to 85 diploma and undergraduate students with prior experience using artificial intelligence for academic activities. The research model included perceived usefulness, ethical awareness, artificial intelligence literacy, and behavioral intention to use. Data were analyzed using partial least squares structural equation modeling with 5,000 bootstrapping resamples to evaluate measurement quality, test direct effects, and assess mediation.Findings – Perceived usefulness significantly predicts behavioral intention to use artificial intelligence tools and also strengthens artificial intelligence literacy. Ethical awareness significantly increases artificial intelligence literacy but does not directly predict behavioral intention. Artificial intelligence literacy significantly predicts behavioral intention and mediates the effects of both perceived usefulness and ethical awareness on intention. These findings suggest that ethical awareness alone may increase caution unless supported by sufficient literacy that enables students to evaluate benefits, limitations, and risks of artificial intelligence tools.Research implications/limitations – The cross-sectional design, purposive sampling, and a single-institution sample limit causal inference and generalizability. Future studies should use larger and more diverse samples and longitudinal designs.Originality/value – This study provides empirical evidence that artificial intelligence literacy functions as a key mediating mechanism linking ethical awareness and perceived usefulness to artificial intelligence usage intention, informing responsible adoption strategies in higher education.